2001
DOI: 10.1016/s0002-9394(01)01218-1
|View full text |Cite
|
Sign up to set email alerts
|

The age-related eye disease study system for classifying age-related macular degeneration from stereoscopic color fundus photographs: the age-related eye disease study report number 6

Abstract: The Age-Related Eye Disease Study has demonstrated satisfactory reliability for detecting onset of advanced age-related macular degeneration in a cohort, and moderate to substantial agreement on various abnormalities across the age-related macular degeneration spectrum. The Age-Related Eye Disease Study system for classification of age-related macular degeneration is suitable for longitudinal multicenter studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
245
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(246 citation statements)
references
References 11 publications
1
245
0
Order By: Relevance
“…All the eyes enrolled had a subfoveal PED larger than one disc area (DA), and the eyes were diagnosed with the wet-type AMD based on the diagnostic criteria proposed by the Age-Related Eye Disease Study research group [15]. According to this classification, the presence of a PED alone indicated that the eye had AMD, regardless of the existence of a CNV.…”
Section: Methodsmentioning
confidence: 99%
“…All the eyes enrolled had a subfoveal PED larger than one disc area (DA), and the eyes were diagnosed with the wet-type AMD based on the diagnostic criteria proposed by the Age-Related Eye Disease Study research group [15]. According to this classification, the presence of a PED alone indicated that the eye had AMD, regardless of the existence of a CNV.…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred normal subjects were used as a control group (normal age-matched). Inclusion criteria were: age >50 years, clear ocular media, and early and intermediate ARMD corresponding to the stages 2 and 3 of the AREDS classification [4]. AREDS stage 2 (early stage in the present study) is characterized by soft drusen with a diameter of ≥63 but <125 µm, drusen total area diameter ≥125 µm, and presence of depigmentation or increased pigment (≥125 µm) of the RPE in the central or inner macular subfields.…”
Section: Methodsmentioning
confidence: 99%
“…The Age-Related Eye Disease Study (AREDS) classified ARMD in 4 stages (early stages 1 and 2, intermediate stage 3 and advanced stage 4) based on stereoscopic color fundus photos [4]. Early and intermediate stages of ARMD are characterized by soft drusen, retinal pigment epithelium (RPE) abnormalities (hyper- and hypopigmentation) and, only in the intermediate stage, RPE atrophy not involving the center of macula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical trials, based on conventional fundus photographs, GA has been defined as a sharply demarcated area of apparent absence of the RPE, larger than 175 µm in diameter, with visible choroidal vessels and no neovascular AMD [5,8,9]. Reduction of retinal thickness due to loss of outer neurosensory cell layers can be visualized by means of stereo fundus photography.…”
Section: Fundus Photographymentioning
confidence: 99%